2021
DOI: 10.1111/jcpe.13524
|View full text |Cite
|
Sign up to set email alerts
|

Association of long‐term obesity and weight gain with periodontal pocketing: Results of the Northern Finland Birth Cohort 1966 study

Abstract: Aim: To investigate whether obesity, central obesity, and weight gain are associated with periodontal pocketing. Materials and methods:A never-smoking sub-population (n = 725) of the Northern Finland Birth Cohort 1966 was categorized based on body mass index (BMI; participants with normal weight, overweight, and obesity) and waist circumference (WC; participants without central obesity and with central obesity) at ages 31 and 46. The categories were combined to define whether the participants stayed in the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…We interpreted the latter to mean that glucose metabolism, as suggested by Genco et al (2005), could be one mechanism through which obesity exerts its effects on the periodontium. This is also in line with our earlier finding of an association between impaired glucose metabolism and periodontal pocketing (Tegelberg et al, 2021). Altogether, the stability of the RRs after adding the above covariates into the models supports the credibility of the findings (Table S5).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We interpreted the latter to mean that glucose metabolism, as suggested by Genco et al (2005), could be one mechanism through which obesity exerts its effects on the periodontium. This is also in line with our earlier finding of an association between impaired glucose metabolism and periodontal pocketing (Tegelberg et al, 2021). Altogether, the stability of the RRs after adding the above covariates into the models supports the credibility of the findings (Table S5).…”
Section: Discussionsupporting
confidence: 93%
“…The data on socio-demographic and health behaviour were collected using a questionnaire at age 46 and categorized as described earlier (Tegelberg et al, 2021). In short, education was categorized into three categories: basic, intermediate and high (ISCED, 1997).…”
Section: Other Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, inconsistent results were reported in prospective cohorts. Several longitudinal studies reported a higher incidence and progression of periodontitis in overweight individuals compared to normal weight individuals (Morita et al, 2011;Gorman et al, 2012;Jimenez et al, 2012;Tegelberg et al, 2021), whereas some others did not find similar associations (Saxlin et al, 2011;de Castilhos et al, 2012). It appears that longitudinal studies with long-term follow-up (≥20 years) can provide more evidence that supports the positive association (Keller et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…BMI and WC, which represent overall obesity and central obesity, respectively, have both been associated with periodontal diseases (Ganesan et al, 2021). Some have suggested that WC is a preferable indicator, because central obesity was found to be more strongly associated with periodontal disease than overall obesity (Kim et al, 2011; Tegelberg et al, 2021). The present MR study found a similar effect size between BMI and WC on the risk of periodontitis/loose teeth.…”
Section: Discussionmentioning
confidence: 99%